The Organization as a Social Self-governing System - GAISINA, Lyutsiya Mugtabarovna; BELONOZHKO, Marina Lvovna; ARTYUKHOV, Andrey Viktorovich; SULTANOVA, Ekaterina Alexandrovna; DALLAKIAN, Galiya Rashidovna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The consequence of the current economic and political environment is not only a high degree of dynamism and mobility of communities, groups, but also social instability and tension of modern society, the growing social exclusion. In such circumstances, the company can consistently exist with the help of a constant internal social environment, which is not static, but constantly developing system of social connections and relationships among employees. Providing high degree of adaptability of enterprise social space becomes an important issue, it is possible if the stable social relations system will be created. It should be suitable for opportunities of internal social structure and consider external social and economic conditions. In this regard there is a necessity for modeling of the specific concepts principles, forms and methods of management oriented to possibilities of domestic enterprises. In this article necessity of a research of all above-mentioned problems is considered. Also the author's representation of a management system is presented, there is the analysis of the management concept, assuming consideration of the self-training entities through a prism of getting of competitive advantages.